A benção às velhas e velhos, eu peço: pedagogia griô e saberes populares ancestrais - Almeida, Adriane Carneiro de (2022)
Accessing ancestral knowledge to think about the expansion of the present is significant if we understand that these references promote rooting of human beings. This factor prevents people from integrating mass society projects. Ancestral knowledge in Brazil is transmitted orally from generation to generation and the practices of production and transmission of this knowledge take place in candomblé terreiros, capoeira school, in sambas de rodas, popular festivals, genres of the Corinthians and repentists, conversations with the/the older/the, etc. The Griô Pedagogy is developed from these knowledges that are from the oral tradition of Brazil. After the activities of Ação Griô Nacional, which has Pedagogia Griô as an inspiring base for its creation, the/the oldest/the masters/es of the knowledge it holds and who participated in its educational actions, have become known as griôs throughout Brazil. The general objective of the research was to understand how griôs, based on popular knowledge, developed educational actions. The research has a qualitative approach, is the type (auto)biographical and the conversation was used as a tool for data production. For listening to five older griôs/the guardians/ões of popular Afro-Brazilian knowledge about their experiences with educational actions in Ação Griô Nacional, We chose to dialogue their speeches and experiences with the discussions of decoloniality and these intersecting with concepts that corroborate to reflect the social role of these subjects: popular knowledge, master/ and oral tradition, Griô, Griô Pedagogy. We understand that epistemic quotas complement ethnic-racial quotas. In this movement the Afro-Brazilian and indigenous narratives of older/those living in the oral tradition become an epistemic reference for knowledge production processes in school spaces and thus it is possible to combat epistemicide. We conclude that it is important these/s older/os in educational processes, especially from the ancestral knowledge, as well as the educational spaces of Ação Griô, contributing to the diffusion and visibility of knowledge that has long been subordinated.